Розробка інформаційної системи зберігання, перегляду та поширення зображень - Лещотний, Є. О. (ХНУРЕ, 2024)
The work discusses the development of an information system designed for creation of online galleries, which enable users to store images and share them with other people. Such services hold significant relevance in modern society, where the widespread use of smartphones facilitates effortless image creation, creating a need for image storage and sharing platforms. The primary strength of this service lies in its exceptionally user-friendly and aesthetically pleasing interface, coupled with its capability to support images of ultra-high resolution, a feature which cannot be provided by competitors.
Keywords: зберігання зображень; перегляд зображень; поширення зображень; інформаційна система; управління медіа